Correlation Study: Curriculum Development, Learning Planning and Technology as Determinants of the Quality of Indonesian Language Learning - Aeni, Nurul; Muljani, Sutji; Suriswo, Suriswo (Journal of English Language and Education, 2025)
This study aims to examine the influence of the implementation of the Merdeka Curriculum, instructional design, and the utilization of educational technology on the quality of Indonesian language instruction in junior high schools (SMP) and Islamic junior high schools (MTs) in the Songgom District, Brebes Regency. Employing a quantitative method with a descriptive and analytical approach, data were collected through questionnaires administered to 30 Indonesian language teachers as respondents. The data were subsequently analyzed using multiple linear regression analysis with the assistance of SPSS version 26. The findings reveal that: (1) The implementation of the Merdeka Curriculum has a statistically significant negative effect on the quality of Indonesian language instruction, indicating the presence of challenges such as teacher readiness and adaptation to curriculum changes. (2) Instructional design exhibits a statistically significant positive effect, underscoring the critical role of well-structured planning in enhancing instructional quality. (3) The utilization of educational technology also demonstrates a statistically significant positive effect, suggesting that the integration of technology contributes to greater instructional effectiveness. Collectively, these three variables account for 57.6% of the variance in instructional quality, while the remaining 42.4% is attributable to factors beyond the scope of this study. The implications of this research emphasize the necessity of comprehensive teacher training to enhance understanding and competence in implementing the Merdeka Curriculum, the development of innovative instructional designs, and the optimal integration of educational technology. Recommendations for schools and policymakers include the provision of supporting infrastructure, training modules, and more intensive dissemination of the curriculum. Consequently, this study contributes to the advancement of Indonesian language instructional quality in the digital era.